2017
DOI: 10.1186/s13071-017-2535-4
|View full text |Cite
|
Sign up to set email alerts
|

Tick-borne pathogens in ticks collected from birds in Taiwan

Abstract: BackgroundA variety of human diseases transmitted by arthropod vectors, including ticks, are emerging around the globe. Birds are known to be hosts of ticks and can disperse exotic ticks and tick-borne pathogens. In Taiwan, previous studies have focused predominantly on mammals, leaving the role of birds in the maintenance of ticks and dissemination of tick-borne pathogens undetermined.MethodsTicks were collected opportunistically when birds were studied from 1995 to 2013. Furthermore, to improve knowledge on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
29
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 111 publications
2
29
0
Order By: Relevance
“…Although not proved in Palestine, migrating birds have been found to carry infected ticks and transfer tick‐borne diseases from one area to another as found in Sweden (Kuo et al . ). Another plausible explanation for the two foci is the climate change.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Although not proved in Palestine, migrating birds have been found to carry infected ticks and transfer tick‐borne diseases from one area to another as found in Sweden (Kuo et al . ). Another plausible explanation for the two foci is the climate change.…”
Section: Discussionmentioning
confidence: 97%
“…The Jordan Valley lying in the middle of the rift is a major point of attraction for these birds to rest in on their way during the spring and autumn annual migration. Although not proved in Palestine, migrating birds have been found to carry infected ticks and transfer tick-borne diseases from one area to another as found in Sweden (Kuo et al 2017). Another plausible explanation for the two foci is the climate change.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, R. raoultii causes tick-borne lymphadenopathy and Dermacentor -borne necrosis and lymphadenopathy [ 77 ]. Kuo et al [ 84 ] recently identified Rickettsia helvetica in eight individual Ixodes columnae larva collected from four local bird species in eastern Taiwan and one migratory bird species captured from 1995 to 2016, also identifying Rickettsia monacensis in one Ixodes nipponesis collected from one local bird species. R. helvetica causes an atypical rickettsiosis similar to R. raoultii [ 77 ], and R. monacensis has been documented to cause an uncharacterized rickettsiosis in North Africa and Korea [ 49 ].…”
Section: Emerging Vector-borne Rickettsiosesmentioning
confidence: 99%
“…The other three sequences detected (RT20, 21, and 23) formed an independent monophyletic group and shared the same branch with Anaplasma spp. detected in Taiwan, South Korea, Morocco, Tunisia, and Poland (Figure ). Although these Anaplasma spp.…”
mentioning
confidence: 98%